1990
DOI: 10.1136/gut.31.2.217
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic activation: a mechanism for morphine induced pain and rises in liver enzymes after cholecystectomy?

Abstract: In patients with biliary type pain after cholecystectomy, morphine often precipitates pain and may induce rises in plasma concentrations of liver enzymes because of exaggerated or prolonged rises in intrabiliary pressure. In this study, changes in plasma concentrations of catecholamines and histamine were determined after the administration of morphine in patients with and without a two-fold or greater rise in the plasma concentration of aspartate aminotransferase at four hours. Those showing rises in aminotra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…In this respect, the mechanism of pain with CCK-8 appears to differ from that with morphine, where sympathetic activation not only accompanies the development of pain but may precede the onset of pain. 7 Since the digestion products of fat and protein in the proximal small bowel are major stimuli to endogenous CCK secretion: the above results could explain the high frequency of fat intolerance in patients with various functional bowel syndromes. Furthermore, improvement in symptoms may follow a reduction in dietary fat andor the use of novel agents such as devazepide which antagonize the effects of CCK on CCKA receptomZ0 ,…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, the mechanism of pain with CCK-8 appears to differ from that with morphine, where sympathetic activation not only accompanies the development of pain but may precede the onset of pain. 7 Since the digestion products of fat and protein in the proximal small bowel are major stimuli to endogenous CCK secretion: the above results could explain the high frequency of fat intolerance in patients with various functional bowel syndromes. Furthermore, improvement in symptoms may follow a reduction in dietary fat andor the use of novel agents such as devazepide which antagonize the effects of CCK on CCKA receptomZ0 ,…”
Section: Discussionmentioning
confidence: 99%
“…Autonomic dysregulation has also been proposed as the cause of the motility disorder. Sympathetic overactivity has been found under basal conditions and during pain episodes in patients with postcholecystectomy pain who develop pain in association with morphine administration (53,54). Furthermore, the severity of the pain in this patient group can be attenuated by clonidine (55), a sympathetic antagonist.…”
Section: Mechanism Of So Dysfunctionmentioning
confidence: 99%
“…Major trauma and severe injury result in post‐trauma stress disorder, which activates the sympathetic system and induces a catecholamine surge . In turn, this pathophysiologic reaction leads to host damage by activating adrenergic β‐receptors.…”
Section: Introductionmentioning
confidence: 99%
“…Major trauma and severe injury result in post-trauma stress disorder, which activates the sympathetic system and induces a catecholamine surge. [3][4][5][6] In turn, this pathophysiologic reaction leads to host damage by activating adrenergic β-receptors. 7,8 Recently, a growing body of research has revealed that activation of β-receptors negatively modulates bone remodelling under physiological conditions 9,10 and impairs bone metabolism and bone fracture healing after trauma.…”
mentioning
confidence: 99%